Combination of experimental measurements and numerical modelling for prediction of ground-borne vibrations induced by railway traffic. (8th August 2022) - Colaço, A.; Castanheira-Pinto, A.; Alves Costa, P.; Fernández Ruiz, J.
Highlights: Evaluation of the dynamic response of a structure to vibrations induced by railway traffic; Presentation of a hybrid methodology, combining numerical/experimental results. Presentation of an experimental case study, including the track-ground-building system. Experimental validation of the hybrid prediction tool. Abstract: Noise and vibration are considered as the biggest externalities of rail transport, increasing conflicts and problems for residents. Versatile and accurate prediction models are essential for the delimitation of problematic cases and the consideration of possible mitigation measures. Regarding the specific case of vibrations, and in order to minimize the uncertainty level associated with the prediction procedure, the formulation of a hybrid approach is presented, combining numerical and experimental results. This approach is applied to an experimental case study, where for the first time this kind of prediction methodologies are fully validated, involving the track, the ground and the building. Also, as a novelty, a deep discussion about the influence of the number of point source transfer mobilities for the line source transfer mobility is presented. For this purpose, different scenarios are analysed, namely the scenario where it is intention the prediction of the vibration levels inside of a planned building or to evaluate the impact of the construction of a new railway track in the vicinity of an existing building. The satisfactory results achieved by the comparison between experimental and estimated results highlight the practical application of the methodology.